MicroRNA expression detected by oligonucleotide microarrays: System establishment and expression profiling in human tissues - Barad, Omer; Meiri, Eti; Avniel, Amir; Aharonov, Ranit; Barzilai, Adi; Bentwich, Isaac; Einav, Uri; Gilad, Shlomit; Hurban, Patrick; Karov, Yael; Lobenhofer, Edward K.; Sharon, Eilon; et al.

(untitled) (Genome Research, 2004)
MicroRNAs (MIRs) are a novel group of conserved short ∼22 nucleotide-long RNAs with important roles in regulating gene expression. We have established a MIR-specific oligonucleotide microarray system that enables efficient analysis of the expression of the human MIRs identified so far. We show that the 60-mer oligonucleotide probes on the microarrays hybridize with labeled cRNA of MIRs, but not with their precursor hairpin RNAs, derived from amplified, size-fractionated, total RNA of human origin. Signal intensity is related to the location of the MIR sequences within the 60-mer probes, with location at the 5′ region giving the highest signals, and at the 3′ end, giving the lowest signals. Accordingly, 60-mer probes harboring one MIR copy at the 5′ end gave signals of similar intensity to probes containing two or three MIR copies. Mismatch analysis shows that mutations within the MIR sequence significantly reduce or eliminate the signal, suggesting that the observed signals faithfully reflect the abundance of matching MIRs in the labeled cRNA. Expression profiling of 150 MIRs in five human tissues and in HeLa cells revealed a good overall concordance with previously published results, but also with some differences. We present novel data on MIR expression in thymus, testes, and placenta, and have identified MIRs highly enriched in these tissues. Taken together, these results highlight the increased sensitivity of the DNA microarray over other methods for the detection and study of MIRs, and the immense potential in applying such microarrays for the study of MIRs in health and disease.